EVALUATION OF A HEAD POSITIONING BANDAGE WITH ELECTRONIC CONTROL IN VITREORETINAL SURGERY RECOVERY - Khikmatullaev B.Kh. (Central Asian Journal of Medicine, 2025)
Postoperative head positioning plays a vital role in optimizing anatomical outcomes following vitreoretinal surgery. This study evaluates the clinical efficacy, safety, and tolerability of a head-stabilizing bandage equipped with an integrated electronic positional controller during the early recovery period. The device continuously monitors head orientation and provides real-time feedback to assist patients in maintaining prescribed positioning, which is critical for appropriate tamponade distribution and chorioretinal adhesion. A cohort of 147 patients with retinal detachment underwent surgery followed by controlled head immobilization using the device for up to 72 hours. Outcome measures included anatomical retinal reattachment, intraocular pressure changes, incidence of hyphema, patient-reported discomfort, and sleep disturbances. The results demonstrate improved adherence to positioning protocols, high rates of retinal reattachment by day 10, and acceptable tolerability across a wide age range. The findings support the potential integration of electronic-assisted positional control into standardized postoperative care protocols for retinal surgery.